Wash-free highly sensitive detection of C-reactive protein using gold derivatised triangular silver nanoplates - GOUNKO, IOURI; BLAU, WERNER; KELLY, JOHN (My University, 2014)
A rapid, wash-free highly sensitive detection method for C-reactive protein (hs-CRP) is reported with both triangular silver nanoplate (TSNP) and Au-edge coated TSNP biosensor sols. The latter shows higher assay sensitivity as well as excellent stability under assay conditions including centrifugation and salinity. A series of Au derived TSNP sols including Au-edge-coated TSNP, AuAg nanomesh and nanobox derived sols are examined as statistically representative saline-stable enhanced ensemble local surface plasmon resonance (LSPR) refractive index sensitive sensors. Samples with plasmon bands spanning the biological spectral window are prepared showing enhancement compared with the original TSNP sols. Refractive index sensitivities as high as 1816 nm RIU−1 are exhibited by Au-edge-coated TSNP sols. The priority of ensemble refractive index sensitivity values over figures of merit in characterising these sols is examined using discrete dipole approximation calculations and single nanostructure dark field microscopy measurements. We anticipate that the high ensemble LSPR refractive index sensitivities, saline stability and ultra-low detection limit capacity of the Au derived TSNP sols, in particular Au-edge coated TSNP sols, present them as excellent candidates for sensing within biological environments.
PUBLISHED
Keywords: C-reactive protein (hs-CRP); C-reactive protein (hs-CRP)